The Factors Affecting Parent’s Preference When Selecting Islamic Schools - Muchamad Fauyan; Puji Yanti Fauziah; Lutfi Wibawa; Nordin Bin Mamat (Universitas Islam Negeri (UIN) Salatiga, 2024)
This research aims to analyze the factors influencing parental preferences in choosing Madrasah Salafiyah Ibtidaiyah (MSI) 14 Medono, focusing on parental characteristics, selection factors, and parental expectations. MSI 14 Medono was chosen due to its reputation as a religious school with a specialized program. This qualitative descriptive study involved parents, school principal, teachers, and students as respondents. Data were collected using questionnaires, interviews, observations, and documentation and analyzed using qualitative and quantitative descriptive approaches. Parental preferences in choosing MSI 14 Medono were accounted for by active learning processes, security, conducive school climate, adequate facilities, information technology, effective leadership, extracurricular options, academic achievements, parental involvement, location, costs, as well as the provision of religious education services such as TPQ and Tahfidz. These findings implies that religious education and character formation are priorities for parents when selecting education for their children. This research also highlights the importance of information technology, effective school leadership, and teacher quality in influencing parental preferences.